Identifying the determining factors of recreation demand in Kongar Lake of South Sumatera: An individual travel cost approach - Suhel, Suhel; Bashir, Abdul; Yuliana, Saadah (Forest and Society, 2019)
Assessing the economic value of natural resources is always challenging and depends on various perspectives. Specifically, this study seeks to identify the determining factors of recreation demand regarding the Kongar Lake of South Sumatera. The data was obtained from a survey of 150 individuals who visited the lake. The approach used descriptive statistics and an individual travel cost method (ITCM) to conduct the investigation of distributional effects across variables on the number of visitors by using a linear multiple regression approach with a natural logarithm model. The findings suggest that (i) joint recreation demand is influenced by travel costs, income, distance, education, age, and work hours per day; (ii) in part the results of this study show that determining factors of recreation demand are based on travel cost, distance, and education; (iii) the consumer surplus was IDR.16,912 per visit and the annual recreational value included 1,720 people who visited the lake annually over an area of 5,298,288 per ha. The results of this study reveal that Kongar Lake has a considerable recreational value that, from this point of view, can help policymakers to make the case for preservation planning and sustainable utilization of natural resources.